One-axis hysteresis motor driven magnetically suspended reaction sphere. (April 2017) - Zhou, Lei; Imani Nejad, Mohammad; Trumper, David L.
Abstract: This paper presents the design, modeling, control, and experimental results for a one-axis magnetically suspended reaction sphere (1D-MSRS) driven by a hysteresis motor. The goal of this work is twofold: (a) to conduct a preliminary study for magnetically suspended reaction sphere for three-axis spacecraft attitude control, and (b) study the potential of hysteresis motors for the reaction wheel/sphere drives. The 1D-MSRS uses a hysteresis motor with a spherical rotor made of solid steel. The rotor sphere is magnetically suspended in all translational directions, and is driven about the vertical axis by a bearingless hysteresis motor. We present the modeling and control of the magnetic suspension of the bearingless motor in the 1D-MSRS, and the hysteresis motor dynamics are analyzed by a hysteresis motor equivalent circuit model. The 1D-MSRS system has experimentally demonstrated a starting torque of 8.9 mNm under 0.7 A peak sinusoidal excitation current. With this excitation the sphere can run up to 12, 000 rpm synchronously in the presence of air drag. This study demonstrates that the hysteresis motor has strong potential for use in high-speed, low-vibration reaction wheels.